Relationship between nutritional status on admission to the intensive care unit and clinical outcomes. Issue 2 (28th September 2020) - Kaddoura, Ranim; Shanks, Alison; Chapman, Marianne; O'Connor, Stephanie; Lange, Kylie; Yandell, Rosalie
Abstract: Aim: To determine the prevalence of malnutrition on admission to the intensive care unit (ICU) and the relationship between nutritional status on admission and clinical outcomes in adult critically ill patients. Methods: This was a prospective study in an adult ICU. Patients with expected length of stay (LOS) >48 hours in ICU were assessed for nutritional status using the patient generated‐subjective global assessment (PG‐SGA) within 48 hours of admission to ICU. Results: Primary outcomes were ICU and hospital mortality, ICU and hospital LOS and length of mechanical ventilation. A total of 166 patients were enrolled in this study. Patients were aged 59 ± 17 years on average with a mean BMI of 29 ± 7 kg/m 2 and a mean Acute Physiology and Chronic Health Evaluation II score of 19 ± 7. The prevalence of malnutrition in critically ill patients was 36% (n = 60). Mortality rate of malnourished patients was 9% (n = 15) compared to 7.8% (n = 13) in well‐nourished patients (adjusted odds ratio, 2.17; 95% confidence interval, 0.9‐5.03, P = .069). There was no difference in hospital mortality between malnourished patients and well‐nourished patients (10.2% vs 10.2% adjusted odds ratio, 1.93; 95% confidence interval, 0.89‐4.19, P = .096). There was no relationship between nutritional status and length of mechanical ventilation (3.0 vs 1.0 days, P = .382)or ICU LOS (4.7 vs 4.8 days, P = .59). Malnourished patients had a longer LOS in hospital than well‐nourished patients (24 vs 17 days, P = .03). Conclusion: Malnutrition is an independent risk factor for increased hospital LOS.